Timothy's Parenting Adaptation as a Christian Education Approach for the Digital Generation - Zalukhu, Amirrudin (Jurnal Teologi Praktika, 2025)
This study explores the adaptation of Timothy's parenting model as a Christian education approach to address the challenges faced by the digital generation. Using a qualitative literature review methodology, it examines biblical principles from Timothy's upbringing, as highlighted in the Pauline epistles, and their relevance to modern educational contexts. The digital generation, characterized by technological dependence, rapid information exchange, and shifting moral values, requires an education model that integrates faith, mentorship, and critical thinking. Timothy's parenting model emphasizes intergenerational mentorship, spiritual grounding, and resilience, offering valuable insights for fostering holistic growth in the digital era. The findings highlight practical strategies for Christian parents and educators, including faith-based digital literacy, relational discipleship, and the cultivation of character through biblically grounded mentorship. These strategies align with the goal of preparing a generation equipped to navigate technological complexities while upholding Christian values. This study contributes to the ongoing discourse on faith-integrated education by providing a framework for bridging biblical principles and contemporary pedagogical practices, paving the way for future empirical research.